Healing the Mountain's Wounds: Reflections on two Chinese site-specific mountain performances. (17th February 2019) - Ke, Shi
Abstract : In this article, I present two short, critical responses to two site-specific mountain performances: Xu Zhen's8848 Minus 1.86 and ten artists'To Add One Metre to an Anonymous Mountain . By introducing social, cultural and political backgrounds and analysing the aesthetic models of the two pieces, I will discuss how performance can be an aesthetic agent that 'inflicts' the 'wounds' that humans make on the natural environment and how a similar performance strategy can also be a way of healing those wounds. Conducting a critical reflection on these two cases, I investigate a certain type of performative strategy symbolized by the metaphor of 'wounds' and 'healing' to re-engage with the issue pertaining to nature and subjectivity. I argue that a performative aesthetic manifestation of an ethical conundrum could be the instrument needed to conduct such a re-engagement. Performance in nature environment sometimes provides cultural landscapes that Adorno rejects as both cultural conservatism and aestheticism. Many current aesthetic-political modalities sometimes fuel the current environmental crisis because of a distanced objectification, which treats nature as material and resource. Although appearing to be the antithesis of such a Cartesian perspective, the Kantian aesthetic actually follows the same logic that inflicts 'wounds' on our environment.8848 Minus 1.86 parodies such a cultural logic of destruction of late capitalism, whileTo Add One Metre to an Anonymous Mountain performs a healing ritual with the irony of a naive nostalgia for an imagined tradition. With its shamanic ludicrousness, performance can transform the objective geographical field into a liminal space of bodily reflectivity, not to provide a total solution but to offer a possibility of re-entering the mountains.